Orthographic Differences between Pietist and Ecclesiastical Publications in the Output of Degens’ Printing Press - Šinkūnas, Mindaugas (Senoji Lietuvos literatūra, 2018)
Late in the eighteenth century, the number of literate people in East Prussia increased, the demand for books was growing, and the printing became cheaper. There appeared the laymen capable of translating relevant religious publications into Lithuanian and preparing them for printing. Most of these people belonged to the Pietist movement and preached the word of God to the surinkimininkai who would gather for prayer in their ordinary homes. Georg Heinrich Bernhard Degen in Königsberg (Karaliaučius) in Prussia printed one of the first, major, and largest of the Pietist publications – Johann Arndt’s six books of Wahres Christentum (True Christianity) in Lithuanian. Degen’s printing house is attributed to small or middle-size publishers that cooperated with beginning and unrecognised authors. The said book consists of 1533 pages; its printing was commissioned and the funds for printing were raised by Pietist preachers. Five years later, the typographer printed two more large Pietist books. After Degen’s death his son turned to the pastors of the official Church. The largest book that came from his press was the third edition of Lithuanian Bible prepared by the pastor Martynas Liudvikas Rėza (1816). Just like the vast majority of the publications of the time, the Bible followed traditional orthography of Lithuania Minor. The orthography used by the surinkimininkai differed from it considerably. The orthographic norms of Lithuanian Evangelical Lutherans became established and were codified in as early as the mid-seventeenth century by the grammars of Danielius Kleinas. A characteristic feature of orthography is the abundance of diacritic marks and marking of morphological forms. Fricative consonants were marked by the letters <ß>, <>; affricates — <cʒ>, occasionally <ć>, and <d>, <dʒ>; the front mid vowel /eː/ was marked <ė>; the long vowel /iː/ —; the diphthong /uo/ — <ů>; four nasal vowels were used <, , , >; the acute accent sometimes marked the stressed syllable and falling intonation diphthongs (letters <á, é>, less often— <ó, ú>); the markers of the morphological forms in the word endings were the letter , the circumflex (<ê, ô, û>), and less often the grave accent (<à, è, ù>). These orthographic principles hardly changed until the nineteenth century. Degen’s first publications indicate the beginning of a new stage in the development of orthography. Most of the traditional orthographic norms are </dʒ></d></cʒ> ignored. Only <ß>, <cʒ>, of the above-mentioned graphemes are used, accent marks and other diacritics are completely ignored, and even the consonant /ʒ/ is marked by a letter without a diacritic mark — <ʒ>. Of the diacritic letters, only <> and <> are irregularly used, sometimes in the position of a preposition or a prefix, and never in the ending. The letter <ů> is extremely rare and is substituted by in the diphthong position. The publications of Degen’s printing house show that alongside the traditional orthography of Lithuania Minor, a simpler orthographic variety evolved. The reasons for the emergence was a change of recipients of the literature. Traditional orthography, which marked phonetic, prosodic, and even some of the morphological features in detail was convenient to German pastors (and even obligatory to those whose knowledge of Lithuanian was poor), but detailed orthography was superfluous to the native Lithuanians. For those readers, the accent marks and the disambiguation of morphological polysemy in the text were of no significance, and simplified orthography made the work much faster for the printer. </cʒ>